Synthesis of Ionic Imprinted Membrane (IIM) Based on Sulfonated Polyeugenol for Selective Transport of Gold (III) Metal Ions from Motherboard Waste - Muhammad Cholid Djunaidi; Fadjrin Nur Rahmayani; Khabibi khabibi (Jurnal Kimia Sains dan Aplikasi, 2022)
Ionic imprinted membrane (IIM) was successfully synthesized using sulfonated polyeugenol, a derivative of eugenol as a functional polymer, with PVA as a base membrane and PEGDE as a crosslinker. IIM Au(III) is a membrane with an Au(III) ion template. This study aimed to determine the pH effect of a feed phase for selective transport of IIM Au(III), comparing it with a non-imprinted membrane (NIM) against Au3+ metal ions from motherboard waste. It also aimed to compare the membrane selectivity of Au3+ metal ions to Cu2+ metal ions, which are also found in motherboard waste. Gold samples were prepared using H(AuCl4) standard and leaching solutions from motherboard waste. The leaching of the motherboard used aqua regia and the assistance of a microwave to accelerate the leaching process. The optimum transport of Au3+ metal ions was when using IIM Au(III) at pH 3. This proved that the presence of a template affected IIM Au(III) to recognize Au(III) ions. IIM Au(III) showed higher selectivity than NIM, as evidenced by the percentage in the receiving phase of the Au3+ metal ions, which was more significant than the Cu2+ metal ions from the motherboard leaching solution.